Seasonal Dynamics Of Aquatic Plants And Physicochemical Factors In An Urban Pond Of Jatrabari, Dhaka (Journal of the Asiatic Society of Bangladesh, Science, 2015)
Samad Nagar pond situated in Jatrabari, Dhaka showed mean air temperature 20 - 30 °C and water temperature 19 - 28°C. Secchi depth (Zs) varied from 28.67 - 44.5 cm and pH 6.6 - 8.8. The mean DO and alkalinity ranged 5.34 - 10.00 mg/1 and 0.58 - 1.08 meq/1, respectively. Free C02, SRP and SRS ranged 1.31 - 4.21 mg/1, 158.39 - 635.70 pg/1 and 13.32 - 28.65 mg/I, respectively. During the study period, seasonal mean values of transparency was higher in monsoon and lower in winter. pH, alkalinity remained higher in winter but lower in monsoon. From aquatic plant communities of the pond, phytoplankton represented by 33 species of which 54.55% belonged to Chlorophyceae (54.55%) followed by Bacillariophyceae (13.64%), Cyanophyceae (13.64%), Euglenophyceae (13.64%) and Dinophyceae (4.55%). The population density of phytoplankton community ranged 6.16 - 25.96>